Effect of green and ripe Carica papaya epicarp extracts on wound healing and during pregnancy - Anuar, Nor Suhada; Zahari, Shaﬁyyah Solehah; Taib, Ibrahim Adham; Rahman, Mohammad Tariqur (Elsevier Limited, 2008)
The traditional use of papaya to treat many diseases, especially skin conditions and its prohibition for consumption during pregnancy has prompted us to determine whether papaya extracts both from green and ripe fruits improve wound healing and also produce foetal toxicity. Aqueous extracts of green papaya epicarp (GPE) and ripe papaya epicarp (RPE) were applied on induced wounds on mice. GPE treatment induced complete healing in shorter periods (13 days) than that required while using RPE (17 days), sterile water (18 days) and Solcoseryl ointment (21 days). Extracts were administered orally (1 mg/g body weight/day) to pregnant mice from day 10 and onwards after conception. 3 (n = 7) mice and 1 (n = 6) mice given RPE and misoprostol, an abortive drug, respectively experienced embryonic resorption while this effect was observed in none of the mice given GPE (n = 5) and water (n = 5). The average body weight of live pups delivered by mice given GPE (1.12 +/- 0.04 g) was significantly lower than those delivered by mice given water (1.38 +/- 0.02 g). In SDS-PAGE, proteins were distributed in three bands (Mr range similar to 8-29 kDa). Band intensity at Mr similar to 28-29 kDa was higher in GPE than in RPE. In contrast, band intensity at low Mr (similar to 8 kDa) was found to be higher in RPE than in GPE. Notably, the band corresponding to Mr similar to 23-25 kDa was absent in RPE. These differences in composition may have contributed to the different wound healing and abortive effects of green and ripe papaya